The Effect of Crime on Tourism in Indonesia - Farhan, Muhammad; Susanti, Hera (Journal of Strategic and Global Studies, 2024)
Tourism sector is widely known as one of economic sectors that can be the engine of economic growth in an effort to reduce poverty in a country. However, growth in the tourism sector can be influenced by safety factors. Tourists tend to avoid tourism destination areas with high crime rates in order to avoid becoming victims of crime. This study aims to analyze the effect of crime on the number of tourist arrivals in Indonesia by using four proxies of crime, which are total crime rate, property crime rate, violent crime rate, and fraud crime rate. This study utilizes a panel data with Fixed Effect Model Within-Group (FEM WG) regression as the main model and Instrumental Variable – Two-Stage Least Squares (IV-2SLS) model to test the endogeneity of the crime variables. The estimation result shows that crime has a negative effect on tourist arrivals in Indonesia. Fraud crime tends to have a stronger effect on tourist arrivals than property and violent crimes. The negative effect of crime tends to be stronger in popular tourism destination areas.